The unconventional role of Akt1 in the advanced cancers and in diabetes-promoted carcinogenesis. (July 2019) - Alwhaibi, Abdulrahman; Verma, Arti; Adil, Mir S.; Somanath, Payaningal R.
Graphical abstract: Abstract: Decades of research have elucidated the critical role of Akt isoforms in cancer as pro-tumorigenic and metastatic regulators through their specific effects on the cancer cells, tumor endothelial cells and the stromal cells. The pro-cancerous role of Akt isoforms through enhanced cell proliferation and suppression of apoptosis in cancer cells and the cells in the tumor microenvironment is considered a dogma. Intriguingly, studies also indicate that the Akt pathway is essential to protect the endothelial-barrier and prevent aberrant vascular permeability, which is also integral to tumor perfusion and metastasis. To complicate this further, a flurry of recent reports strongly indicates the metastasis suppressive role of Akt, Akt1 in particular in various cancer types. These reports emanated from different laboratories have elegantly demonstrated the paradoxical effect of Akt1 on cancer cell epithelial-to-mesenchymal transition, invasion, tumor endothelial-barrier disruption, and cancer metastasis. Here, we emphasize on the specific role of Akt1 in mediating tumor cell-vasculature reciprocity during the advanced stages of cancers and discuss how Akt1 differentially regulates cancer metastasis through mechanisms distinct from its pro-tumorigenic effects. Since Akt is integral for insulin signaling, endothelial function, and metabolic regulation, we also attempt to shed some light on the specific effects of diabetes in modulating Akt pathway in the promotion of tumor growth and metastasis.